Synthesis of 3,7-Dihydroxy-3,7-dioxopenhydro-1,5,3,7-diazadiphosphocines with Various Amines - Lee, Y.G.; Lee, U.S.; Yang, J.W.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2014)
As a part of a research program related to the synthetic study of pharmacologically interesting compounds and good chelating agent for transition metal ion, we here report the synthesis of an unusual medium-sized ring heterocyclic ligand with mixed carboxylic-amino-phosphonic donating groups. We have synthesized 1,5-diphenyl-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4a), 1,5-di(2-ethaneamine)yl-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7- diazadiphosphocine (4b), 1,5-dibenzoic acid-yl-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4c), 1,5-difurfuryl-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4d), 1,5-di[thiophene-2ylmethyl]-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4e), 1,5-di[thiophene-2yl]-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4f), 1,5-dipyridin-4-yl-3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine (4g), 3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine-1,5-diacetic acid (4h), 2-[5-(1,2-dicarboxyethyl-3,7-dihydroxy-3,7,dioxo-315.715-[1,5,3,7]diazadiphosphocan-1-yl]-succinic acid (4i) and 3,7-Dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine-1,5-di-(2-glutaric acid) (4j).